GARLIC PRODUCTION IN UKRAINE: CURRENT SITUATION AND PROSPECTS - Зуйкова, Анна; Томашевская, Ольга (SWorldJournal, 2022)
The level and dynamics of garlic production in Ukraine are studied, perspective directions of the industry development are outlined.